Qual é a “SUAS”? A terapia ocupacional e o Sistema Único de Assistência Social - Oliveira, Marina Leandrini de (2020)
Social assistance was established as a field that sought to avoid disruption of the social fabric, thus preserving the contradictory capitalist logic, in addition to outlining a history marked by welfarism, philanthropy and volunteerism as main guidelines, in a long process until its recognition as a right. In Brazil, the paths towards the composition of social assistance as a public policy of State intervention culminated in the recent organization of the Unified Social Assistance System (SUAS) in 2005. During its implementation, which occurred by means of Resolution no. 17, 2011, of the National Council on Social Assistance, the possibility of insertion of occupational therapists as part of the team and management of SUAS was made official, and such professionals were recognized. In view of the recent officialization of this category and the absence of nationally compiled data on professional insertion and practice in the sector, this study aimed to identify, describe and analyze the characteristics of professional insertion and the practices developed by occupational therapists in the social assistance units that compose the SUAS network. To this end, the methodological procedures were organized in two stages: one associated with a survey of the number of professionals working in the SUAS and another focused on the description and analysis of their insertion and practices, with the latter structured in three parts, as follows: 1) Online questionnaires – after completion of Stage I, when 1323 occupational therapists linked to social assistance were identified in 2016, professionals were contacted by telephone and invited to participate in the study by responding to the online questionnaire, and 242 forms were obtained; 2) Interviews – ten of these respondents were interviewed, and the interviews were recorded and transcribed; 3) Visits – four 5-day visits were made to social assistance units to observe the practices of occupational therapists, which were recorded in field diaries. Results from the different stages provided a set of information on the professionals regarding their insertion (region of the country, social assistance unit, employment bond, function, workload, schooling, and professional training) and developed practices (objectives of the interventions, types of assistance/follow-up, resources and activities used, among others). Association of these data with those made available by the Brazilian Ministry of Social Development in 2017 revealed that occupational therapists working in social assistance are predominantly female (n=93%), practice in the Southeast region (n=60%), in outpatient clinics (n=53%), with official employment bond (n=50%), and a 30-hour weekly workload (n=30%). As for qualitative data, these professionals develop various interventions, according to the particularities of the different units, namely, reception, workshops, individual and family follow-ups, home visits, and intersectoral network articulation. It was identified that such practices occur according in/with everyday lives, and are aimed at expanding the social support networks of users at the primary and secondary levels, paving ways to contribute to social protection. In conclusion, occupational therapists are linked to the SUAS as practitioners within the social assistance policy, and contribute to meeting to the demands of the sector and the needs of the population, in order to foster promotion of social protection.